Induced breeding and management practices for mass seed production of nutrition-sensitive mola carplet (Amblypharyngodon mola) - Ali, Hazrat; Dubey, Sourabh; Biswas, Ashutosh; Jaman, Ahmed; Rashid, Harun (WorldFish, 2024)
The practical guideline ‘Induced Breeding and Management Practices for Mass Seed Production of Nutrition-Sensitive Mola Carplet (Amblypharyngodon mola)’ has been developed under the CGIAR Initiative on Asian Mega-Deltas. This user-friendly manual outlines a step-by-step protocol for the induced breeding of mola, addressing the lack of standardized techniques that previously limited its widespread adoption. It also includes essential guidance on seed nursery management, packaging, and transportation systems to ensure successful seed production and distribution. The nine-step process is designed for easy adoption by fish hatcheries, facilitating the scaling up of nutrition-sensitive aquaculture practices and contributing to food security initiatives in regions where mola holds significant nutritional value.